Shear performance of single embedded nut bolted shear connectors in precast steel–UHPC composite beams under combined tension-shear loads - Bingxiong Xian; Guodong Wang; Feiyang Ma; Shu Fang; Haibo Jiang; Jiajun Xiao (Case Studies in Construction Materials, 2024)
Steel-ultra-high-performance concrete (UHPC) composite beams employing single embedded nut bolted shear connectors (SENBs) in full-depth precast concrete deck systems represent a competition attempt in recent years, which can fully utilize the exceptional material characteristics of both SENBs and UHPC. Due to the demountable SENBs, this innovative composite beam could be easily deconstructed to repair or recycle deteriorated components. However, the composite beams can generally combine tensile and shear loads during the service stages. Nevertheless, limited investigations concentrated on the shear performance of SENBs in precast steel–UHPC composite beams under combined tension-shear loads. For this purpose, nine push-out tests and theoretical analyses were performed in this paper, considering the influence of bolted diameter and the tensile-to-shear ratio. The experiment results demonstrated that the bolted diameter substantially affected the shear performance of the SENBs in terms of ultimate shear strength, stiffness, and ductility. In addition, the tensile-to-shear ratio had a limited influence on the shear strength and ductility of SENBs but an insignificant impact on their failure modes. Finally, more precise design models were suggested to forecast the tensile-shear relationship and relationship of load-slip by SENBs in precast steel-UHPC composite beams under combined tensile-shear loading.